2021
DOI: 10.3389/fmats.2021.640102
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Structural Configurations of Magnetorheological Fluid Based Devices Reported in 2018–2020

Abstract: Magnetorheological fluid (MRF) is a kind of smart materials with rheological behavior change by means of external magnetic field application, which has been widely adopted in many complex systems of different technical fields. In this work, the state-of-the-art MRF based devices are reviewed according to structural configurations reported from 2018 to 2020. Based on the rheological characteristic, the MRF has a variety of operational modes, such as flow mode, shear mode, squeeze mode and pinch mode, and has un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 113 publications
2
27
0
Order By: Relevance
“…6(a) that under the same magnetic field, shear stress increases with the increase of the shear strain rate and carrier viscosity. On the one hand, the higher the carrier viscosity, the greater the average deflection angle of chains; on the other hand, with the increase of the shear strain rate, the drag effect on the particle chains increases, increasing the average deflection angle of particle chains, which is consistent with the description given by eqn (11). Therefore, the average deflection angle of particle chains (i.e.…”
Section: Experimental Verification and Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…6(a) that under the same magnetic field, shear stress increases with the increase of the shear strain rate and carrier viscosity. On the one hand, the higher the carrier viscosity, the greater the average deflection angle of chains; on the other hand, with the increase of the shear strain rate, the drag effect on the particle chains increases, increasing the average deflection angle of particle chains, which is consistent with the description given by eqn (11). Therefore, the average deflection angle of particle chains (i.e.…”
Section: Experimental Verification and Discussionsupporting
confidence: 83%
“…[4][5][6] Because of the excellent rheological and mechanical properties, MRFs have a wide range of applications in aerospace, mechanical engineering, medical engineering, and other fields, such as dampers, brakes, clutches, magnetic resonance imaging materials, and lower limb prostheses. [7][8][9][10][11][12][13] Shear stress is an important index to evaluate the rheological properties of an MRF, as well as the influencing factor, and has been studied by many researchers. For example, Vicente et al investigated the effect of particle shape on yield stress through experiments and finite element calculations and showed that the rod-like particle based MRFs have a larger storage modulus and yield stress compared with their spherical and plate-like counterparts, which means that the particle shape significantly influences the MR performance.…”
Section: Introductionmentioning
confidence: 99%
“…Phu and Choi presented a mini-review article on MR brakes and clutches reported from 2013 to 2018 with a focus on their structural configurations [63]. Hua et al reviewed the state of the art based on the structural configurations of MR brakes and clutches developed between 2018 and 2021 [64]. In this section, MR brakes and clutches developed from 2015 to 2021 are summarized according to their fields of application.…”
Section: Mr Brake/clutchmentioning
confidence: 99%
“…The yield stress of MR fluid is a well-controlled parameter utilized in various MR fluid applications where the fluid experiences high shear strain rates, e.g., damping and torque control devices (Carlson and Jolly 2000). The high performance and potential of the technology maintain the interest of many researchers in the development and improvement of the smart fluid and devices based on it (Kumar, et al, 2019;Phu and Choi 2019;Hua, et al, 2021). However, the variable modulus, another viscoelastic parameter of MR fluid, has received less attention in literature (Wang and Meng 2001).…”
Section: Introductionmentioning
confidence: 99%